Indoor air quality, thermal comfort and ventilation in deep energy retrofitted Irish dwellings. (1st July 2022) - Coggins, Ann Marie; Wemken, Nina; Mishra, Asit Kumar; Sharkey, Martin; Horgan, Liam; Cowie, Hilary; Bourdin, Emmanuel; McIntyre, Brian
Abstract: Residential building stock energy retrofits will play a key role in EU climate actions. The impact of these retrofits on indoor air quality (IAQ) and occupant comfort needs to be assessed to inform future renovation programmes. This study evaluated IAQ and occupant satisfaction in a sample (n = 14) of deep energy retrofitted Irish residences, at least 12 months post retrofit. Measurements of PM2.5, formaldehyde, total volatile organic compounds (TVOCs), carbon monoxide, radon, and carbon dioxide were made in the main bedroom and living area over a period of two days to three months (depending on the pollutant). Temperature and humidity in most homes were within design comfort limits. Higher concentrations of all pollutants were measured in bedrooms. Only 30% of bedroom data met EN16798 Category I limits for CO2 (within 380 ppm of outdoor concentrations), suggesting that bedrooms maybe under ventilated. Median formaldehyde concentrations of 25.4 and 20.7 μg/m 3 were detected in bedroom and living rooms respectively, with building materials likely being the major source. All radon data (apart from one home located in a high radon area) was less than the national reference value of 200 Bq/m 3 . Measured ventilation extract flow rates in most participating homes would not meet the minimum performance requirements in Irish Regulations of 2019 – introduced post completion of the retrofits in this study. Greater compliance with the ventilation requirements of retrofits and the promotion and use of low emitting construction materials are recommended. Highlights: 14 retrofitted Irish domestic dwellings were assessed for IAQ and occupant satisfaction. Multiple thermal and IAQ parameters were measured in the main living room and bedroom. Higher concentrations of all measured pollutants were measured in bedrooms. Human activities had an important impact on pollutants like PM2.5 Testing and validation of mechanical ventilation systems is crucial for retrofitting.